Joe Sweet: serving patients with the support of our strong Cleveland Clinic team - Wang, Molly J. (Journal of Hospital Management and Health Policy, 2018)
Mr. Joe Sweet is Director of International Patient Experience, Cleveland Clinic. As a busy leader who is often travelling for work he enjoys time spent outdoors to relax himself; running, cutting the grass, walking the dog, riding bike, playing ball with his kids. He enjoys running outside a few times per week to clear his mind and re-energize (Figure 1).